Different trajectories of neurological soft signs progression between treatment-responsive and treatment-resistant schizophrenia patients. (June 2021) - Lui, Simon S.Y.; Yip, Stanley S.L.; Wang, Ya; Hung, Karen S.Y.; Ho, Karen K.Y.; Tsang, Kirby C.M.; Yeung, Hera K.H.; Cheung, Eric F.C.; Chan, Raymond C.K.
Abstract: Schizophrenia patients exhibit subtle and non-localizing neurological abnormalities, known as neurological soft signs (NSS). Life-span evidence suggests that NSS vary along the course of schizophrenia. An association between NSS and treatment response has been proposed, suggesting that NSS reflect the underlying neuropathology development in schizophrenia. However, few studies have investigated the relationship between NSS and treatment resistance in first-episode schizophrenia patients. We conducted a longitudinal study on 52 first-episode schizophrenia patients, who were assessed at baseline, the sixth month, and the fifth year using the abridged version of the Cambridge Neurological Inventory. The trajectories of NSS between 29 treatment-responsive patients (with full symptomatic remission) and 23 treatment-resistant patients (who received clozapine) were compared using mixed model ANOVA. We also controlled for the effect of age and estimated IQ, using a mixed ANCOVA model. Although the two schizophrenia groups had comparable NSS at the baseline, their trajectories of NSS differed significantly. Compared with their treatment-responsive counterparts, treatment-resistant schizophrenia patients had worsening of NSS over time. Our findings support the potential utility of NSS in identifying treatment resistance in first-episode schizophrenia. Progressive worsening of NSS in treatment-resistant schizophrenia patients may reflect the development of underlying neuropathology. Further studies using large samples of treatment-resistant schizophrenia patients are needed. Highlights: The levels of neurological soft-signs fluctuated in both treatment-responsive and treatment-resistant schizophrenia patients. Treatment-resistant SZ patients exhibited worsening of NSS with time, compared with treatment-responsive SZ patients. Our findings support the potential clinical utility of NSS as a marker associated with treatment-response. Despite two markedly contrast groups of treatment-resistant and treatment responsive SZ were used, the sample size was small.